The Positive Effect of Authoritarian Leadership on Employee Performance: The Moderating Role of Power Distance - Wang, Honglei; Guan, Bichen (Frontiers in Psychology, 2018)
Based on goal setting theory, this study explores the positive effect and influencing process of authoritarian leadership on employee performance, as well as the moderating role of individual power distance in this process. Data from 211 supervisor-subordinate dyads in Chinese organizations indicates that authoritarian leadership is positively associated with employee performance, and learning goal orientation mediates this relationship. Furthermore, power distance moderates the effect of authoritarian leadership on learning goal orientation, such that the effect was stronger when individual power distance was higher. The indirect effect of authoritarian leadership on employee performance via learning goal orientation is also moderated by power distance. Theoretical and managerial implications and future directions are also discussed.